Superficial CD34-positive fibroblastic tumor: A new entity; case report and review of literature - Neelam Sood; Binit Kumar Khandelia (Wolters Kluwer Medknow Publications, 2017)
Earlier, categorized under low grade malignant fibrous histiocytoma and low grade sarcomas, 'superficial CD34 positive fibroblastic tumor', a newly proposed entity, is a low grade mesenchymal tumor of intermediate malignant potential. Morphological features include monomorphic neoplastic spindle cells arranged in a fascicular to storiform pattern along with sheets of pleomorphic epithelioid cells, and multinucleated giant cells with glassy cytoplasm. Diffuse vimentin and characteristic diffuse CD34 positivity is seen in all cases with few showing focal cytokeratin expression. Rest of the melanocytic and mesenchymal markers are negative. Herein, we present a case of superficial CD34-positive fibroblastic tumor in arm swelling of a 16-year-old female. Differential diagnosis of the same on the basis of morphology as well as immunohistochemistry has also been discussed. This is the first case reported from India to the best of our knowledge.